The Correlation of Communication Effectiveness and Patient Satisfaction. (3rd March 2021) - Versluijs, Yvonne; Lemmers, Maartje; Brown, Laura E.; Gonzalez, Amanda I.; Kortlever, Joost T. P.; Ring, David
This study assessed the correlation of 9 questions addressing communication effectiveness (the Communication Effectiveness Questionnaire [CEQ]) with other patient-reported experience measures (PREMs; satisfaction, perceived empathy) as well as patient-reported outcome measures (PROMs; pain intensity, activity tolerance) in patients with musculoskeletal illness or injury. In a cross-sectional study, 210 patients visiting an orthopedic surgeon completed the CEQ and measures of satisfaction with the visit, perceived empathy, pain intensity, and activity tolerance. We evaluated correlations between CEQ and other PREMs and CEQ and PROMs. We measured ceiling effects of the PREMs. Communication effectiveness correlated moderately with other PREMs such as satisfaction (ρ = 0.54; P < .001) and perceived empathy (ρ = 0.54; P < .001). Communication effectiveness did not correlate with PROMs: pain intensity (ρ = −0.01; P = .93) and activity tolerance (ρ = −0.05; P = .44). All of the experience measures have high ceiling effects: perceived empathy 37%, satisfaction 80%, and CEQ 46%. The observation of notable correlations of various PREMs, combined with their high ceiling effects, direct us to identify a likely common statistical construct (which we hypothesize as "relationship") accounting for variation in PREMs, and then develop a PREM which measures that construct in a manner that results in a Gaussian distribution of scores. At least within the limitations of current experience measures, there seems to be no association between illness (PROMs) and experience (PREMs).